Preparation and DFT Study for New Three-Ring Supramolecular H-Bonded Induced Liquid Crystal Complexes - Mohammady, Sayed Z.; Aldhayan, Daifallah M.; Hagar, Mohamed (Frontiers in Chemistry, 2021)
Supramolecular three ring Schiff base novel liquid crystal complexes have been prepared and investigated. Schiff bases of para substituted aniline derivatives and para pyridine carbaldehyde have been prepared and then mixed in equimolar quantities with para alkoxy benzoic acids. On one side, the alkoxy chain length varies from eight to sixteen carbon atoms. On the other side, terminal small compact groups substituting aniline with various polarity are used. Hydrogen bonding interaction was elucidated by FTIR spectroscopy. The mesomorphic thermal and optical characteristics of the samples were obtained by differential thermal analysis (DSC) and polarized optical microscopy (POM). All samples exhibit enantiotropic mesophases. Experimental results obtained for the induced mesophases were correlated with density functional theory (DFT) theoretical calculations. The Results revealed that both the polar compact groups polarity and the alkoxy chain lengths contribute strongly to mesomorphic characteristics and thermal stabilities of the mesophases. Surprisingly, the observed values of enthalpy changes associated with the crystalline mesomorphic transitions lie in the range of 2.2 to 12.5 kJ/mol. However, the enthalpy changes corresponding to the mesomorphic isotropic transitions vary from 0.9 to 13.9 kJ/mol depending on the polarity of para attached groups to the aniline moiety.